Plano de segurança contra incêndio e pânico em uma empresa madeireira - Höfle, Henrique Edalos (2012)
This work was themed display equipment and technologies for the prevention and fire protection in general, identifying the essential elements and the conditions for existence of fire. Studying what is this fire and its transformation into fire, how is its development; phases; classification and their classes. The same also presents a study on standardization and legislation relating to fire protection and prevention in timber company in this case has been studied. That work also presents the techniques and methods of extinguishing existing. It is described on the preventive aspects of readequamento and Lumber, starting with the project, its implementation, through the execution phase of the work and its completion.